A 3D Innovative Approach Supporting the Description of Boring Sponges of the Precious Red Coral Corallium rubrum - Pulido Mantas, T.; Bavestrello, G.; Bertolino, M.; Cerrano, C.; Pica, D.; Roveta, C.; Calcinai, B. (Journal of Marine Science and Engineering, 2022)
The carbonatic scleraxis of Corallium rubrum (L.), commonly known as red coral, is often found infested by excavating sponges. These boring organisms produce galleries inside the compact axis of the coral in a variety of shapes compromising the integrity of the skeleton and reducing its commercial value. Three sponge species, already known to bore into Corallium rubrum, have been identified in colonies collected from Cape Verde Archipelago—Alectona millari (Carter, 1879); Dotona pulchella mediterranea (Rosell and Uriz, 2002); and Thoosa armata (Topsent, 1888)—together with a new species belonging to the genus Alectona and here described. SEM analysis provided evidence of the microerosion patterns of these species, confirming the presence of radial scars overlapped with the concentric ones, in T. armata. For the first time, microcomputed tomography was employed to obtain three-dimensional reconstructions of sponge excavations inside the red coral scleraxis and to estimate the eroded volume